Influence of inlet gas volume fraction on performance of a gas-liquid centrifugal pump. Issue 6 (March 2019) - Yan, S N; Luo, X Q; Zhang, L F; Feng, J J; Zhu, G J; Chen, S L; He, D H; Li, C H
Abstract: In order to study the influence of inlet gas volume fraction on performance of a gas-liquid centrifugal pump, the CFD commercial software ANSYS CFX 16.0 was used to solve the three-dimensional turbulent flow field in a gas-liquid two-phase flow centrifugal pump. The non-homogeneous two-fluid model was chosen for the purpose of obtaining phase distribution and its influence on the pressure and velocity fields, and the SST k-ω model was chosen as turbulence model. The result showed that the performance of the pump is stable under single-phase flow operating points. Under gas-liquid two phase flow, with the increase of inlet gas volume fraction, the pressure increment would be reduced, and the internal flow would be unstable. As the inlet gas volume fraction reaches a certain value, surge would occur under small flow rate conditions. At this time, a large amount of gas was concentrated in the impeller flow channel, and the channel of the impeller was blocked evenly, which lead to the pump's head dropped suddenly. Under design flow and large flow rate operating points, with the inlet gas volume fraction increase, the performance of the pump was relatively stable, and the head of the pump decreases slowly.